1966
DOI: 10.4992/psycholres1954.8.131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlordiazepoxide Upon Partially-Reinforced Behavior of Rats in the Straight Runway

Abstract: Runway performance of rats was studied as a function of reinforcement schedule (100% reward vs. 50% reward) and drug dosage level (10 mg/kg, and 20 mg/kg, i.p. of CDP, and saline). The groups injected with 10 mg/kg of CDP ran faster on initial trials than the other groups, but slightly slower on later trials than the corresponding saline groups. The 50% reward saline group was superior in speeds in early trials but much inferior in later trials to the 100% reward saline group. A similar finding was obtained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

1967
1967
1982
1982

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
4
5
0
Order By: Relevance
“…In both cases the trial was concluded. In the present study, only the RT data were analyzed since practically identical results (with larger variations) were obtained in terms of ST as was the case in our previous study (Iwahara et al, 1966).…”
Section: Methodssupporting
confidence: 63%
See 2 more Smart Citations
“…In both cases the trial was concluded. In the present study, only the RT data were analyzed since practically identical results (with larger variations) were obtained in terms of ST as was the case in our previous study (Iwahara et al, 1966).…”
Section: Methodssupporting
confidence: 63%
“…The main effect associated with this reward variable was highly significant (F=30 .69, df=1/37; ance with most of the previous results with normal undrugged rats, and it has been called the partial-reinforcement effect (PRE) as revealed in extinction (e.g., Lewis, 1960), which, however, must be distinguished from the PRE as revealed in acquisition. The latter PRE was found to be inhibited by amobarbital (Wagner, 1963), ethyl alcohol (Nelson & Wollen, 1965) and CDP (Iwahara et al, 1966).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These data are already well documented (Hulse, 1958;Wagner, 1961) and need no further discussion, other than to mention that the frustration account has been used to interpret these results. The finding that pretrial injections of CDP lead to slower running times in acquisition and retarded extinction has also been previously reported (Iwahara, Iwasaki, Nagamura, & Masuyama, 1966;Iwahara, Nagamura, & Iwasaki, 1967). Similar results have been found using the pharmacologically related drugs amobarbital sodium (Rosen, Glass, & Ison, 1967;Wagner, 1963) and ethanol (Nelson & Wollen, 1965).…”
Section: Discussionsupporting
confidence: 83%
“…This dosage was established as the optimum for producing anxiety reduct ion in conflict situations while minimizing ataxia . Iwahara, Iwasaki, Nagamura, and Masuyama (1966), for example, noted that rats in a straight runway exhibited sluggish locomotor behavior and ataxia with dosages of 20 mg/kg of CDP but not with 10 rng/kg.…”
Section: Pharmacological Agentmentioning
confidence: 99%